THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL SUPPORT, PROACTIVE PERSONALITY, AND AI LITERACY ON TASK PERFORMANCE: THE MEDIATING ROLE OF WORK ENGAGEMENT IN CHINA - Wang, Xi; Kamarul Zaman, Maliza Delima (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
As artificial intelligence (AI) increasingly transforms the manufacturing industry, understanding the human factors that influence task performance is vital. This research explores how transformational leadership, perceived organizational support, proactive personality, and AI literacy influence task performance among employees in manufacturing companies in Hunan Province, China. Grounded in Self-Determination Theory (SDT), the research examines the satisfaction of employees’ needs for autonomy, competence, and relatedness promote work engagement, which serves as a mediator in these relationships. The study adopts a quantitative methodology, with the intention of collecting the data through structured surveys from employees in AI-integrated manufacturing companies in China. Statistical Package for the Social Sciences (SPSS) and Structural Equation Modelling (SEM) will be utilized to analyse the direct and indirect impacts of the independent variables on task performance via work engagement. The data will be collected and analysed, and the results are expected to indicate that transformational leadership, organizational support, proactive personality, and AI literacy significantly enhance task performance, both directly and indirectly, by boosting work engagement as hypothesized in this research. This research advances current knowledge by applying SDT in AI-enabled workplaces and is expected to offer practical recommendations for managers seeking to enhance employee motivation and task performance amid technological change.